PECULIARITIES OF NATIONAL ATTITUDES TOWARDS MONEY IN THE ENGLISH-SPEAKING PICTURE OF THE WORLD AND BEYOND - Amonov Sunatillo Nusratovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The situation in the English-speaking world is completely different. Money is an important component of the culture of society there. It is also obvious that money performs the function of social ranking of members of society and serves as a tool for identifying an individual in the space of social hierarchies.